2021
DOI: 10.1002/onco.13845
|View full text |Cite
|
Sign up to set email alerts
|

Real-WorldClinical Outcomes in Patients with Locally Advanced or Metastatic Merkel Cell Carcinoma Treated in U.S. Oncology Clinical Practices: Results fromSPEAR-Merkel

Abstract: Background. Immunotherapies (IO) have been associated with improved outcomes in patients with locally advanced Merkel cell carcinoma (laMCC) and metastatic MCC (mMCC). The primary objective of SPEAR-Merkel was to explore treatment patterns, clinical outcomes, and healthcare resource utilization (HCRU) in patients with laMCC or mMCC initiating first-line (1L) treatment with avelumab, non-avelumab IO, or chemotherapy in a US community oncology setting. Methods. Adult patients with laMCC or mMCC initiating 1L ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Indeed, the first-line response rate for MCC (~56–62%) is essentially the highest among solid tumors. 31–35 Across multiple trials, the response rate has been similarly high for both VN-MCC and VP-MCC patients. 3 16 36 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, the first-line response rate for MCC (~56–62%) is essentially the highest among solid tumors. 31–35 Across multiple trials, the response rate has been similarly high for both VN-MCC and VP-MCC patients. 3 16 36 …”
Section: Discussionmentioning
confidence: 98%
“…Indeed, the first-line response rate for MCC (~56-62%) is essentially the highest among solid tumors. [31][32][33][34][35] Across multiple trials, the response rate Open access has been similarly high for both VN-MCC and VP-MCC patients. 3 16 36 VP-MCC has frequently been used to understand the immunological correlates of response and tumor antigenspecific T cells, due to the invariant MCPyV oncoprotein antigens expressed by these virally driven tumors.…”
Section: Discussionmentioning
confidence: 99%
“…This approval was based on the results of the international phase 2 JAVELIN Merkel 200 study, which demonstrated the effectiveness of avelumab both in patients with chemotherapy‐refractory metastatic MCC (Study Part A) 12 and as first‐line treatment in patients with metastatic MCC (Study Part B) 13,14 . Since then, several retrospective studies have also published real‐world data on avelumab use in MCC as a first‐ or second‐line treatment, confirming findings from the JAVELIN Merkel 200 study 4,8,15–17 …”
Section: Introductionmentioning
confidence: 73%
“…13,14 Since then, several retrospective studies have also published real-world data on avelumab use in MCC as a firstor second-line treatment, confirming findings from the JAVELIN Merkel 200 study. 4,8,[15][16][17] As only three Japanese patients were enrolled in the pivotal JAVELIN Merkel 200 study, post-marketing surveillance (PMS) was required to confirm the safety and effectiveness of avelumab for its approval in Japan. The current PMS presents the results of first-line treatment of avelumab in patients with MCC from an unbiased, allcase surveillance.…”
Section: It Has Since Been Approved In Numerous Countries Includingmentioning
confidence: 99%
“…The results from SPEAR-Merkel, the first study to evaluate real-world clinical outcomes in 94 patients with la-MCC and m-MCC receiving first-line avelumab ( n = 28), non-avelumab immunotherapies ( n = 26, 19 pembrolizumab, 7 nivolumab), or chemotherapy ( n = 40), also highlight the therapeutic value of avelumab with an overall response rate of 64.3% and a median PFS of 11.4 months, compared to 61.5% with a median PFS of 8.1 months in the non-avelumab immunotherapy group and 42.5% with a median PFS of 6.1 months in patients undergoing chemotherapy [ 105 ]. In a similar real-world setting study involving a cohort of 20 patients with advanced MCC, comparable results were reported (overall RR: 65%; overall median time to treatment failure: 22 months) [ 106 ].…”
Section: The Role Of Immunotherapy In Non-melanoma Skin Cancermentioning
confidence: 99%